P229 Adjunctive treatment with oral AKL1, a botanical nutraceutical, in chronic obstructive pulmonary disease. (14th November 2013) - Brockwell, C; Ampikaipakan, S; Sexton, D; Price, D; Freeman, D; Thomas, M; Ali, M; Wilson, AM
Abstract : Background: Treatment for chronic obstructive pulmonary disease (COPD) includes both bronchodilating and anti-inflammatory therapies. However majority of patients with COPD show corticosteroid resistance and alternative therapies are need. AKL1 is a patented botanical formulation containing extracts of Picrorhiza kurroa, Ginkgo biloba, and Zingiber officinale which has shown anti-inflammatory effects in vitro . Methods: We undertook a randomised double-blind, placebo-controlled trial to determine the safety and efficacy of AKL1 in patients with a clinical labelled diagnosis of COPD and Leicester Cough Questionnaire (LCQ) score of <17. The 10-week study period comprised a 2-week single-blind placebo run-in period followed by add-on treatment with AKL1 or placebo twice daily for 8 weeks. The primary study end-point was the change from week 0 to week 8 in cough-related health status, as assessed by the LCQ. Secondary endpoints were St. George's Respiratory Questionnaire, MRC dyspnea score, forced expiratory volume in 1 second (FEV1) and 6 minute walk test. Results: Of 33 (19 male) patients mean (SD) age of 67 (9.4) years 57.9 (17.2) FEV1% predicted enrolled into the study, 15 (45%) patients were smokers and 16 (49%) were ex-smokers. Twenty patients were randomised to AKL1 and 13 to placebo. The mean (SD) change from baseline in LCQ score at 8 weeks was 2.3 (4.9) in the AKL1 group and 0.6 (3.7) in the placebo group (p = 0.43). The St. George's Respiratory Questionnaire score improved significantly more in the AKL1 treatment group (mean [SD], -7.7 [11.7]) than in the placebo group ( + 1.5 [9.3]; p = 0.042). There were no significant differences between treatment groups in change from baseline to week 8 in other patient-reported measures, lung function, or the 6-minute walk distance. Five patients reported adverse events. Chest infections were diagnosed in one patient in each treatment allocation group. In the AKL1 group, one patient reported nightmares and one patient had right shoulder pain at the baseline visit; and one patient had influenza at the final visit. Conclusion: Further study is needed with a larger patient population and over a longer duration to better assess the effects of add-on therapy with AKL1 in COPD